2014
DOI: 10.1007/s00221-014-4114-7
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplasticity of imagined wrist actions after spinal cord injury: a pilot study

Abstract: Motor imagery (MI - i.e., the mental representation of an action without physically executing it) stimulates brain motor networks and promotes motor learning after spinal cord injury (SCI). An interesting issue is whether the brain networks controlling MI are being reorganized with reference to spared motor functions. In this pilot study, we tested using magnetoencephalography (MEG) whether changes in cortical recruitment during MI were related to the motor changes elicited by rehabilitation. Over a 1-year per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…Articles without movement performance assessment (Enzinger et al, 2008 ; Di Rienzo et al, 2014b , 2015 ; Faller et al, 2014 ; Scherer et al, 2015 ; Tidoni et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Articles without movement performance assessment (Enzinger et al, 2008 ; Di Rienzo et al, 2014b , 2015 ; Faller et al, 2014 ; Scherer et al, 2015 ; Tidoni et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, long-term effects of MI training probably help to overcome these experienced troubles, as has been suggested by Gustin et al ( 2008 ). Furthermore, it is important to note, that this does not mean that the ability to perform MI is impaired, as it has been reported that MI vividness in patients with SCI is comparable to that of healthy subjects (Hotz-Boendermaker et al, 2008 ; Di Rienzo et al, 2014b , c , 2015 ; Fusco et al, 2016 ; Roosink et al, 2016 ). Additionally, we investigated visual and kinesthetic MI and it is possible that MI strategies may change after SCI (Fiori et al, 2014 ).…”
Section: Discussionmentioning
confidence: 96%
“…It is found that MI shares the similar cognitive processes [ 1 ] and sensory motor cortical [ 2 ] with movement execution. Therefore, MI is widely used for motor learning, such as in a variety of sports, e.g., rhythmic gymnastics [ 3 ], badminton [ 4 ] and slalom [ 5 ], and in rehabilitation of patients who cannot do active movements after a stroke [ 6 ], spinal cord injury [ 7 ], or Parkinson’s disease [ 8 ]. MI has also been a widely used strategy of brain computer interface (BCI) for controlling an unmanned aerial vehicle [ 9 ] or robot arm [ 10 ].…”
Section: Introductionmentioning
confidence: 99%